Critical Review of Social Safety Net in COVID Era Based on Maqashid Sharia Framework: Indonesia Case - Tika Widiastuti, - (2020)
The high number of layoffs, bankruptcy, and increased poverty has forced the government to provide Social Safety Nets (SSN) programs to the public suffered from the COVID-19 pandemic. Problems arise when SSN programs failed to reach the basic needs of society. This paper aims to provide a Critical Review Analysis of the SSN program, especially in the COVID-19 pandemic, based on the Maqashid Sharia framework. This study used a qualitative approach with a case study analysis to provide a critical review of government policies in managing the COVID 19 pandemic. The data obtained from government policy literature such as Indonesia Laws from March-July 2020. The finding shows that from five aspects of Maqashid Sharia (Protecting Religion, Soul, Intellect/Mind, Heredity and Wealth), the Indonesia Government focuses on protecting the soul and wealth. This problem causes the non-optimal performance of the government when handling COVID 19 pandemics. The paper contributes to the government decision making for the SSN Program based on the the Maqashid Sharia